2005
DOI: 10.1111/j.1468-3083.2004.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of cutaneous angiosarcoma of the face and scalp and treatment with placitaxel

Abstract: Cutaneous angiosarcoma (AS) of the face and scalp of the elderly is a rare malignant tumour with a very poor prognosis. The variable presentation and the benign appearance of the cutaneous AS may often delay the correct diagnosis. Because it is extremely aggressive, only early detection and treatment can modify the prognosis. We describe a case of an old man who was diagnosed of AS of the face and scalp 1 month after developing the cutaneous lesion. After treatment with placitaxel, the lesion completely dimini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Skin and superficial soft tissue are the most common locations (60% of cases) [2] with high rate of lymph node and systemic metastasis and reported 5-year survival of 10% to 35% [3]. …”
Section: Discussionmentioning
confidence: 99%
“…Skin and superficial soft tissue are the most common locations (60% of cases) [2] with high rate of lymph node and systemic metastasis and reported 5-year survival of 10% to 35% [3]. …”
Section: Discussionmentioning
confidence: 99%
“…In most of the cases, treatment is administered on a weekly basis and affects scalp or skin AS. In that setting, most of the reports describe complete or partial responses with short progressionfree survival up to 3-4 months [17][18][19][20][21][22][23]. Angiosarcoma of liver [11] Particularly frequent in industrial workers exposed to vinyl chloride (used in the production of synthetic rubber) Frequent in workers exposed to insecticides, such as arsenics Primaries arose from viscera in 8 cases; from breast in 10 cases; and from soft tissue, skin or, scalp in 12 cases.…”
Section: Treatment Of Metastatic Angiosarcomasmentioning
confidence: 99%
“…Numerous case reports suggest some kind of clinical benefit with paclitaxel [17][18][19] or docetaxel [20][21][22][23] in patients with unresectable or metastatic AS. In most of the cases, treatment is administered on a weekly basis and affects scalp or skin AS.…”
Section: Treatment Of Metastatic Angiosarcomasmentioning
confidence: 99%
“…In most of the cases reported taxanes were given once weekly and led to complete or partial responses with short progression-free survival up to 3-4 months. 3,8,9 Recently, a phase II clinical trial was conducted, which showed the benefit of weekly paclitaxel in 30 patients with unresectable or metastatic AS. In agreement with previous studies the authors reported a median time to progression of 4 months and a median overall survival of 8 months.…”
mentioning
confidence: 99%